Managing for heterogeneity reduces fire risk in boreal forest landscapes : A model analysis - Zelnik, Yuval R.; Launiainen, Samuli; Vico, Giulia (Elsevier, 2025)
Boreal forests are susceptible to direct and indirect human impacts, which are intensified by climate change. Amidst these challenges, wildfires are increasingly shaping forest dynamics. Boreal forest management must be adapted to mitigate such risks. It is still unclear whether management practices such as using smaller stands, species mixtures and avoiding ditching can effectively mitigate wildfires. We develop a cellular-automata simulation approach and couple it with minimalist litter and plant water balance models to examine the influence of stand size, species composition (conifers vs. broadleaf-deciduous species), and ditching impact on fire spread. We find that smaller forest stand sizes greatly reduce landscape fire risk, where for instance, decreasing stand size from 100 to 1 hectares leads to a fivefold reduction in fire risk. Diversifying tree species composition and avoiding landscape ditching can further reduce fire risk, especially when stand size is large. The effect of forest heterogeneity on fire risk is comparable to that of variability of environmental factors such as air humidity, highlighting the importance and potential of forest heterogeneity in fire mitigation. Our model allows us to explore the complex interactions that govern wildfire behavior in intensively managed boreal landscapes, supporting wildfire risk assessments and informing the development of more sustainable and climate resilient forest management strategies.
Keywords: fire spread; forest management; landscape; spatial heterogeneity; disturbance